Firm Value Ditinjau Dari Pengaruh Kebijakan Dividen dan Growth Opportunity Serta Peran Moderasi Struktur Modal - Rodhiyah, Ma'rufatur; Nur Ani, Heti; Askhar, Bayu Malikhul (Akuntansi dan Manajemen, 2024)
Company value plays an important role, especially in the eyes of investors, because company value reflects company performance which can influence investors' behavior and investment desires in a company. This research was conducted with the aim of finding out how debt policy and growth opportunity influence company value which is moderated by capital structure. This research uses a quantitative approach using secondary data in the form of company financial reports. The population in this research is coal sub-sector companies listed on the IDX in 2019-2023. The sampling technique used was purposive sampling to obtain 39 research samples. The analysis in this research uses the analytical technique of Descriptive Statistical Test, Classical Assumption Test and Moderated Regression Analysis (MRA) which is processed using SPSS software. The research results show that partially dividend policy, growth opportunity and capital structure have an influence on company value, while capital structure is able to moderate the relationship between growth opportunity and company value and capital structure is able to moderate the relationship between debt policy and company value.